The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s40807-016-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of an inclined flat plate-type solar water distillation system

Abstract: Flat plate-type solar water distillation (FPSWD) is having importance for providing hot water and drinking water simultaneously to households in rural areas or small community/hotels. It utilizes solar radiation to heat the water, produce fresh water out of the saline or brackish water, and also produce hot water. The paper is focused on field performance of inclined FPSWD for domestic and commercial applications. Field Performance data of inclined FPSWD has been recorded during summer and winter. It observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…They improved the thermal efficiency with low cost. Sahoo et al (2016) investigated experimentally several parameters such as solar tilt global radiation, hot water temperature, the flow rate of water distillation and the flow rate of hot brackish of water distillation. Ullah et al (2017) concluded that when the ambient temperature is low, double glass cover heat preservation effect is more obvious and the instantaneous efficiency is highest.…”
Section: Introductionmentioning
confidence: 99%
“…They improved the thermal efficiency with low cost. Sahoo et al (2016) investigated experimentally several parameters such as solar tilt global radiation, hot water temperature, the flow rate of water distillation and the flow rate of hot brackish of water distillation. Ullah et al (2017) concluded that when the ambient temperature is low, double glass cover heat preservation effect is more obvious and the instantaneous efficiency is highest.…”
Section: Introductionmentioning
confidence: 99%